Prolonged femoral compression post percutaneous coronary intervention leading to deep vein thrombosis - Amer Abu-Shanab; Jillianne Unas; Hamzeh Nasr; Zain Albdour; Ahmad Abdulraheem; Doantrang Du (European Journal of Case Reports in Internal Medicine)
Deep vein thrombosis is an uncommon yet significant complication of percutaneous coronary interventions. Prolonged manual compression at the access site, a common practice for achieving hemostasis, can inadvertently exacerbate thrombosis risks, including venous stasis and endothelial injury. We present the case of an 84-year-old female with coronary artery disease who underwent staged percutaneous coronary intervention with stent placement in the left circumflex and left anterior descending arteries. After the procedure, manual pressure was applied to the femoral access site for over 30 minutes, after which the patient developed hypotension and leg pain. Point-of-care ultrasound revealed a large deep vein thrombosis in the right femoral vein, extending into the profunda and saphenous veins. The patient was treated with a heparin drip and monitored without surgical intervention. Her condition improved, and follow-up imaging confirmed resolution of the deep vein thrombosis. This case underscores the risks associated with extended manual compression and highlights the importance of adhering to guidelines for post percutaneous coronary intervention care. The use of vascular closure devices may reduce the likelihood of such complications. Additionally, early recognition and management of deep vein thrombosis is critical in preventing further thromboembolic events and improving patient outcomes.